Impact of ethnocentrism on interethnic interactions among local students in Malaysian universities - Ketab, Somayeh Mortazavi Ganji; Tamam, Ezhar; Bolong, Jusang; Sharif, Saeed Pahlevan (Taylor's Business School, Taylor's University, 2015)
In this study, the authors examine the influence of ethnocentrism on offline and online interethnic interactions among Malaysian students at two multiethnic and multicultural Malaysian public universities. The responses of 200 Malay, 105 Chinese, and 38 Indian undergraduate students were analysed. Results reveal a significant difference between the level of offline and online interethnic interactions among respondents. It was found that students had more offline interethnic interactions compared to online interactions. This is due to the fact that interactions through online media are more dependent on a conscious choice and decision to communicate actively and to take the step for interethnic communication. Thus in situations where they could choose whether or not to interact, they presumably willingly elected to not take that step. It can be concluded that students were uninterested in making any effort in expanding their interethnic interaction in the virtual world beyond their own ethnic group due to their ethnocentric attitudes. Therefore, all hypotheses of this study were accepted.